Ethically Minded Consumer Behavior, Brands’ Commitment to Sustainable Development and Brand Equity in the Apparel Market of Pakistan - Ali, Dr. Rizwan; Shah, Syed Raza Ullah; Shahzadi, Sadaf; Ali, Asif; Mirza, Salman (The journal of contemporary issues in business and government, 2022)
Purpose-The current research paper elaborated effect of ethically-minded consumer behavior on the brand pledge to sustainable development and consumer perception and how it further impact “brand equity-loyalty-word of mouth statement. Designing/Methodology/Approach - To evaluate proposed hypotheses, a quantitative study method with a close-ended questionnaire was structured to collect the responses with the convincing non-probability sampling method. About six hundred questionnaires were distributed among the various people and 217 valid responses were received back. To measure the participants’ response, 5- Point Liker Scale was employed. Smart PLS was used to analyses the collected data Findings - The findings of the study recommend and allow an increasing series of suggestions for the brand holders to adopt sustainable development practices and it will raise the attention of the ethically minded consumers. Research Limitations/Implications - The research was conducted in the cities of Punjab Pakistan. Where the level of education and earnings are high. This study should also be conducted in other cities of Pakistan. The researchers have conducted this study for the apparel industry it should also be conducted on the other industries. At the final note for the further study in line with this study mediated relationship between variables used in this proposed model should be done. The new variable can also be introduced like brand image, satisfaction, perceived quality. This study has several implications for managers and academia. As a result of exposure and information, consumer behavior has changed in Pakistan and requires that organizations and brands must take necessary steps for owing sustainable development goals. This pledge to sustainable development is completely supposed by the consumer to boost brand equity, Loyalty, and constructive word of mouth. Originality/Value - To the best of Author’s Knowledge no study has been conducted to measure the impact of consumer behavior on Brands commitment to sustainable development in the Apparel Market of Pakistan